Irrigation ditch. - United States. Army. Signal Corps (photographer):::Creator::::::::::::; Flaherty, John Melvin (collector):::Contributor::::::::::::
Photograph shows evacuees working on an irrigation ditch. Evacuees are using shovels and pickaxes to work.